2023
DOI: 10.1108/jbim-03-2022-0154
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supply chain finance on sustainability performance: empirical analysis and fsQCA

Abstract: Purpose In the context of global economic downturn and intense competition, firms are increasingly resorting to supply chains to acquire capital support and achieve sustainability. This study aims to investigate the effect of supply chain finance (SCF) on corporate sustainability performance (CSP) and identifies SCF-related recipes for CSP. Design/methodology/approach Based on a sample of 1,038 firms that disclose CSP – namely, corporate financial performance (CFP) and environmental, social and governance pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 99 publications
1
4
0
Order By: Relevance
“…effects, and empirically investigated the RDM's effects on environmental, social welfare, and sustainability in emerging economies. The results of the above two research methods are mutually verified, which improves the credibility of our findings (Wang et al, 2023).…”
Section: Theoretical Implicationssupporting
confidence: 78%
See 3 more Smart Citations
“…effects, and empirically investigated the RDM's effects on environmental, social welfare, and sustainability in emerging economies. The results of the above two research methods are mutually verified, which improves the credibility of our findings (Wang et al, 2023).…”
Section: Theoretical Implicationssupporting
confidence: 78%
“…By providing a quantitative approach, it enhances our understanding of development law and aids in making predictions. To enhance the robustness of results and improve the credibility of conclusions, the quasi replication method can be employed as well as (Wang et al, 2023). This method involves testing the validity of the model and replicating the analysis using different datasets or alternative methodologies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies such as Hofmann et al (2019), Vu et al (2022) and Bi et al (2022) also found that SCF significantly affects supply chain financing and organisational performance. Recent studies also established a relationship between SCF and corporate sustainability performance (Wang et al , 2023). Factors such as collaboration, digitisation, information sharing and financial institutions enable better SCF adoption, which eventually leads to supply chain effectiveness (Beka Be Nguema et al , 2020).…”
Section: Introductionmentioning
confidence: 99%